BOE203 -Microscopy and Histological Techniques (Mikroskopi dan Teknik Histologi) - PPSKJ, Pusat Pengajian Sains Kajihayat (Pusat Pengajian Sains Kajihayat, 2024)
First Semester Examination 2023/2024 Academic Session February 2024 BOE203 -Microscopy and Histological Techniques (Mikroskopi dan Teknik Histologi) Duration : 2 hours (Masa : 2 jam)